Effect of fermentation time and temperature on the of polyphenol compounds change of different Congou black tea. Issue 10 (25th August 2021) - Wu, Xiaofen; Ozawa, Tetsuo; Li, Yinhua; Duan, Jihua; Zhu, Kun; Huang, Jianan; Liu, Zhonghua; Wang, Keqin
Abstract: This study evaluated the effects of fermentation time and temperature on the content of high molecular weight polyphenol mitochondrial activation factors (MAFs) and other polyphenols in Congou black tea using high‐performance liquid chromatography (HPLC). There were two broad chromatographic peaks in the HPLC spectra of MAFs: MAFs‐1 (16.163 min) and MAFs‐2 (34.31 min); MAFs‐2 was satisfactorily analyzed by HPLC, with separation by paper chromatography. The MAFs‐2 contents increased gradually in different varieties of Congou black tea as the fermentation time and temperature increased; the maximum MAFs‐2 content was 5.11% in Xiaoxianghong 21‐3 after 8 hr of fermentation. The total polyphenols and catechins contents decreased, whereas the theabrownins contents increased as the fermentation time and temperature increased; the theaflavins and thearubigins contents in different Congou black teas showed different variation tendencies. Therefore, studies regarding changes in polyphenols during fermentation will help improve the quality of Congou black tea and enhance its health benefits. Novelty impact statement: A new method for the determination of MAFs‐2 by high‐performance liquid chromatography combined with paper chromatography was established. The content of MAFs‐2 increased initially and then stabilized as fermentation was continued from 2 to 8 hr, it increased gradually as the fermentation temperature was increased from 23 to 37°C. These results provide a new analytical method for MAFs in black tea and a theoretical basis and technical guidance for improving the quality of Congou black tea.